2006
DOI: 10.1099/jmm.0.46558-0
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of tea-tree oil against clinical skin isolates of meticillin-resistant and -sensitive Staphylococcus aureus and coagulase-negative staphylococci growing planktonically and as biofilms

Abstract: The susceptibility of Staphylococcus aureus [meticillin-resistant (MRSA) and meticillin-sensitive (MSSA)] and coagulase-negative staphylococci (CoNS), which respectively form part of the transient and commensal skin flora, to tea-tree oil (TTO) was compared using broth microdilution and quantitative in vitro time-kill test methods. MRSA and MSSA isolates were significantly less susceptible than CoNS isolates, as measured by both MIC and minimum bactericidal concentration. A significant decrease in the mean via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
44
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 36 publications
(37 reference statements)
12
44
1
3
Order By: Relevance
“…Although there was no significant difference, we observed that MSSA strains were more resistant or showed the same sensibility levels as the MRSA strains for most EO. Brady et al 45 reported similar results when they evaluated the susceptibility of MRSA and MSSA strains to tea tree EO Melaleuca alternifolia and reported MIC between 0.25 to 2.0 v/v and 0.5 -2.0 v/v, respectively, although statistically significant difference was not found for both S. aureus strains. The EO M. piperita has demonstrated antibacterial activity at concentrations of 0.064 to 0.128 mg/mL against MSSA and from 0.064 to 0.256 mg/ mL against MRSA strains, although no significant differences were found between the bacterial types tested 46 .…”
Section: Resultssupporting
confidence: 53%
“…Although there was no significant difference, we observed that MSSA strains were more resistant or showed the same sensibility levels as the MRSA strains for most EO. Brady et al 45 reported similar results when they evaluated the susceptibility of MRSA and MSSA strains to tea tree EO Melaleuca alternifolia and reported MIC between 0.25 to 2.0 v/v and 0.5 -2.0 v/v, respectively, although statistically significant difference was not found for both S. aureus strains. The EO M. piperita has demonstrated antibacterial activity at concentrations of 0.064 to 0.128 mg/mL against MSSA and from 0.064 to 0.256 mg/ mL against MRSA strains, although no significant differences were found between the bacterial types tested 46 .…”
Section: Resultssupporting
confidence: 53%
“…Biofilm formation was also inhibited when oregano essential oils, carvacrol and thymol, were used against S. aureus (99). Five of nine biofilms formed by coagulase-negative staphylococci (CoNS) strains were completely eradicated when 5% tea tree oil (TTO) was used, while the same concentration of TTO achieved complete eradication of methicillin-susceptible S. aureus (MSSA) and MRSA biofilm growth as microcolonies in glycocalyx during 1 h of treatment (100). The antimicrobial function of TTO was attributed to the disruption of the hydrophobic phospholipid bilayers in the cell membrane.…”
Section: Essential Oils: Broad-spectrum Compositions Multiple Mechanmentioning
confidence: 97%
“…In general, bacteria growing within biofilms are more difficult to eradicate than their planktonic counterparts and this may be one of the factors contributing to the relatively long time that it can take to improve acne after commencement of treatment [36]. Whilst no data exist for tea tree oil and P. acnes biofilms, the oil has activity against biofilms of other Gram-positive bacteria such as Staphylococcus aureus [37], suggesting that in principle it may also affect P. acnes biofilm.…”
Section: Properties Of Tea Tree Oil Contributing To Clinical Efficacymentioning
confidence: 97%